ANXIETY IN CATHERINE COOKSON'S THE NICE BLOKE: A PSYCHOANALYTIC APPROACH - WIBOWO , HANAFI (2007)
The major problem of this study is how anxiety is reflected in the major character's personality. The aim of this study is to analyze Catherine Cookson's The Nice Bloke based on the structural elements and the development of personality of the major character based on Psychoanalytic Approach. This study focuses on the major character, namely Harry Blenheim. The benefit of the study is to give additional information which can be used by other literature researchers who are interested in analyzing this play. This study uses two data sources, namely primary and secondary data source. The primary data source is the novel itself, while the secondary data are taken from some information needed. The method of data collection is qualitative method. Based on analysis, the outcome of this study shows that the problem of major characters encounters causes the conflict of his mental condition. Then, it develops to become anxiety and influences him to do some ways to escape from it. Then his ways are not effective to overcome the problem because finally he was taken into prison.